El Niño Southern Oscillation (ENSO) Phenomenon and the Analysis of Time Series Variability in Precipitation within the Guanacaste Conservation Area, Costa Rica - Vega-Araya, Mauricio (2024)
The Pacific Northwest of Costa Rica is a region with marked seasonality in rainfall patterns. This area of Costa Rica is prone to extreme hydroclimatic phenomena such as droughts and floods. Due to the limited distribution of rainfall gauges and the unavailability of relevant information, complementary data obtained from satellites and their respective reanalyzes become imperative for acquiring crucial information. This information can support water resource management actions and their impacts on both natural and productive ecosystems. To analyze the precipitation patterns, we utilized the CHIRPS product’s precipitation time series for five ecoregions within the Guanacaste Conservation Area, located in the northwestern Pacific region of Costa Rica. These curves were strongly and negatively correlated with time series from sea surface temperature monitoring regions, including Niño 1.2, Niño 3, Niño 3.4, and Niño 4. All analyzed ecoregions exhibited strong negative correlations with the Niño 1.2 region, with correlation coefficients (R values) ranging between -0.72 to -0.74. Additionally, a lag of four to five months was observed in the Niño 4 curve compared to the Niño 1.2 region. This study suggests that the Niño 4 anomaly, with a lag of approximately 4 to 5 months, can serve as an indicator of possible impacts on precipitation patterns in different ecoregions. This provides sufficient time to plan actions, particularly within the agricultural sector. This study demonstrates the potential predictability of the effects of ENSO phenomenon on precipitation patterns for large areas with a certain eco-systemic homogeneity, such as the ecoregions in the Guanacaste Conservation Area.